Preload loss of CFRP bolted joint without rotation under transverse and axial loading. (January 2023) - Yang, Haoran; An, Luling; Chen, Xu; Zou, Liyang
There are a large number of CFRP-steel bolted joints with jet nuts subjected to transverse and axial load in aircraft structures, which have passed standard testing of locking characteristics of fasteners under transverse loading conditions. This fastener has a great preload loss and no rotation loosening occurs. Based on the observation, we designed a biaxial loading experiment for CFRP bolted joint, and measured the preload and loosening angle under different initial preload. The biaxial research suggests that compared with the uniaxial loading condition, the preload loss is larger, the rotation is minimal and only appears in the early stage of test, and there are obvious indentations on the surface of CFRP panel. Embedment as an important factor leads to the preload loss due to the weak ability of CFRP panel suffering out of plane load. In order to study the effect of embedment, the relationship between stress S22 and indentation depth under different preload, the relationship between biaxial load amplitude and embedding depth, and the ratio of the preload loss caused by embedding to the total preload loss are revealed by finite element analysis.